Changes in Muscular Fitness and Its Association with Blood Pressure in Adolescents - Garcia-Hermoso, A (Springer Verlag, 2018)
The aims of this study were to examine the longitudinal association between muscular fitness (MF) and blood pressure (BP) 2 years later, and to determine whether changes in MF over a 2-year period were associated with BP at follow-up, in adolescents. The sample comprised 734 youths (349 girls) aged from 12 to 18 years. MF was assessed with the standing long jump and handgrip tests. Socioeconomic status, pubertal stage, waist circumference, resting BP, and cardiorespiratory fitness were measured according to standard procedures. Regression analyses showed a significant inverse association between MF at baseline and systolic BP (β = − 0.072; p = 0.032) and rate pressure product (β = − 0.124; p < 0.001) at follow-up, after adjustments for age, sex, height, pubertal stage, and socioeconomic status. However, when analyses were further adjusted for waist circumference and cardiorespiratory fitness, these associations did not remain significant. Adolescents with persistently high and increasing MF exhibited the lowest levels of diastolic BP (F (3, 721) = 3.814, p = 0.018) and systolic BP (F (3, 721) = 3.908, p = 0.014) when compared to those with persistent low MF after adjustment for age, sex, height, socioeconomic status, cardiorespiratory fitness, and waist circumference. Conclusion: This study suggests that persistent greater and increasing MF in youth are associated with lower levels of BP across the adolescence.What is Known:• Currently, there is a growing interest on the health benefits of muscular fitness.• Cross-sectional studies have identified an association between muscular fitness and blood pressure in adolescents.What is New:• Changes in muscular fitness during adolescence were associated with systolic and diastolic BP over a 2-year period.• Adolescents with persistently low muscular fitness exhibited the highest levels of diastolic and systolic BP. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.